Antidiabetic and antihyperlipidemic activity of ethanol extract of Ekor Naga leaves (Rhaphidophora pinnata (L.f) Schott ) in alloxan-induced male white rats - Fathnur Sani K; Yuliasati Yuliawati; Havizur Rahman; Agung Giri Samudra (Universitas Ahmad Dahlan, 2022)
Antidiabetic and antihyperlipidemic have a very close relationship for Mellitus Diabetics. In previous research, Ekor Naga leaves (Rhaphidophora pinnata (L.f) Schott) had an antihyperglycemic effect. The effect was obtained from the presence of secondary metabolites, namely alkaloids, flavonoids, tannins, saponins, and steroids. This research is expected to be a further test of the antidiabetic and antihyperlipidemic effects of alloxan-induced male white rats. This research used an experimental method. The treatment group was divided into four groups, namely negative control (Na CMC 0,5%), positive control (10 mg/kg BW of glibenclamide), group one (250 mg/kg BW of Ekor Naga leaves extract), and group two (500 mg/kg BW of Ekor Naga leaves extract). Data were taken from blood sugar levels on the days 0th, 7th, 10th, and 14th. Total cholesterol, triglyceride, LDL, and HDL levels were observed on the 14th day. Results were analyzed by one-way ANOVA test. The followed by Duncan’s test. The result of ethanol extract from Ekor Naga leaves showed antidiabetic and antihyperlipidemic activity in alloxan-induced rats, which had a statistically significant difference relative the negative control (p<0,05) decreased the levels of blood glucose, total cholesterol, HDL, LDL, triglycerides. Where the best group is two (500 mg/kg BW of Extract) and followed by group one (250 mg/kg BW of Extract). We concluded that Ekor Naga leaves extract provides activity in the treatment option for patients with diabetes and hyperlipidemia.